ANALISIS SISTEM PENJUALAN PEMASARAN PRODUK PADA PT.PANASONIC GOBEL INDONESIA CABANG MEDAN - Samsul Bahri Siagian; Muhammad Sowban Adilla (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2021)
Panasonic Gobel Indonesia is a company that is active in the sale and marketing of electronic goods for the needs of the public and business. The company cannot be separated from the sales process. Selling is an activity or a business selling products, which is an activity aimed at finding buyers, influencing, and prioritizing buyers so that purchases can match the desired goods. However, the authors here limit the discussion to only focus on the sale (marketing) of goods between dealers and companies both in terms of product input. Therefore, the author aims to analyze the sales process and marketing of goods at PT. Panasonic Gobel Indonesia. When analyzing and collecting data on sales of goods was made, a case was discovered in PT. Panasonic Gobel Indonesia Medan Branch is still experiencing problems in terms of sales of goods, and also errors in inputting product data which result in having to apply repetitive processes for inputting product sales data, and also too many process codes that must be understood by employees in inputting data. Therefore, the authors decided to analyze the product sales application system through a flowchart that can make it easier for employees to do their jobs. That way a product sales application system flow is created which is implemented in the form of a flowchart. With the flow chart so that human errors can be minimized to facilitate employees in sales performance at PT. Panasonic Gobel Indonesia Medan Branch. Keywords: analysis, system, sales flow chart, SAP